GIVE A LISTEN: STORIES OF STORYTELLING IN SCHOOL (Editors: Anne M. Trousdale, Sue A Woesthoff, Marni Schwartz) - Isherwood, Judith (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1995)
Anne M. Trousdale, Sue A Woesthoff, Marni Schwartz (Editors). GIVE A LISTEN: STORIES OF STORYTELLING IN SCHOOL. Urbana. Il: National Council of Teachers of English (1994). 136 pp. $12.95. ISBN 0-8141-1846-1.